How to manage the online experience concerning transactional and experimental customers: case of e-fashion sector - Castro-Lopez, Adrian; Vazquez-Casielles, Rodolfo; Puente, Javier (Journal of Business Economics and Management, 2019)
The online fashion and textile sector is growing in recent years, becoming one of the online sectors with the highest volume of business. However, the bibliography on e-service quality and its consequences in this sector has been underdeveloped in the last years. This paper presents a model that incorporates the direct and indirect effects of e-service quality (utilitarian and hedonic experience) on satisfaction and loyalty of two segments of customers: transactional and online experimental customers. This research focuses on six online sale platforms, and it has been tested with data on 405 regular customers. The study also develops a model that incorporates the direct and indirect effect of e-service experiences on satisfaction, positive WOM, repurchase intention and price tolerance. The findings indicate that direct and indirect effects of e-service quality on satisfaction and loyalty are different for each segment of customers. While utilitarian quality is more relevant for those customers that only search for information, hedonic quality is especially significant for experiential customers.